2005
DOI: 10.1080/13691050412331271416
|View full text |Cite
|
Sign up to set email alerts
|

Public tolerance, private pain: Stigma and sexually transmitted infections in the American Deep South

Abstract: This pilot telephone survey sought to identify social barriers to treating sexually transmitted infections (STIs) in a socially conservative state (Alabama, USA). The sample consisted of 250 household residents aged 19-50 years, mostly African-American and White, who were drawn from the general population. The participants reported that infected persons, per se, should not be stigmatized. However, almost half of respondents stated that they would seek revenge against a partner who infected them. Feelings of em… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
36
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(38 citation statements)
references
References 16 publications
1
36
0
1
Order By: Relevance
“…For example, patients with stigmatized illnesses suffer from negative psychological and social effects, such as depression, anxiety, low self-esteem, reduced social support, and avoidance of social interactions (Crandall and Coleman 1992;Crandall and Moriarty 1995;Kaplan and Toshima 1990;Wright 1983). In addition, research on sexual illness stigma indicated that negative perceptions of sexually transmitted infections (i.e., STI) reduce the likelihood of seeking adequate treatment options (Duncan et al 2001;Fortenberry et al 2002;Lichtenstein et al 2005). Fife and Wright (2000) further demonstrated that patients' with HIV/ AIDS perceived themselves as stigmatized at a greater level and have lower self-esteem levels than those experiencing other serious illnesses.…”
Section: Introductionmentioning
confidence: 98%
“…For example, patients with stigmatized illnesses suffer from negative psychological and social effects, such as depression, anxiety, low self-esteem, reduced social support, and avoidance of social interactions (Crandall and Coleman 1992;Crandall and Moriarty 1995;Kaplan and Toshima 1990;Wright 1983). In addition, research on sexual illness stigma indicated that negative perceptions of sexually transmitted infections (i.e., STI) reduce the likelihood of seeking adequate treatment options (Duncan et al 2001;Fortenberry et al 2002;Lichtenstein et al 2005). Fife and Wright (2000) further demonstrated that patients' with HIV/ AIDS perceived themselves as stigmatized at a greater level and have lower self-esteem levels than those experiencing other serious illnesses.…”
Section: Introductionmentioning
confidence: 98%
“…5,6 In Lichtenstein, Hook, & Sharma's (2005) community survey, respondents were unlikely to notify their sexual partners if they feared being labeled as immoral or sexually deviant. 13 They were also likely to delay or avoid treatment for fear of being classified as members of a stigmatized group (e.g., STI clinic attendees). For the present study, the two constructs were operationalized in items about damaged reputation and moral weakness of character for seven infections ranging from least serious (pubic lice) to most serious (HIV/AIDS).…”
Section: Introductionmentioning
confidence: 99%
“…People living with HIV/AIDS from the Deep South are predominantly African-American, have low levels of education, live in poverty, lack health insurance and have acquired HIV infection through heterosexual contact (Reif, Geonnotti, & Whetten, 2006;. The male:female ratio tends to be more balanced and the social climate for both genders is generally one of stigma, embarrassment and fear, which, together with distrust of the healthcare system, pose substantial barriers to accessing healthcare (Krawczyk et al, 2006;Lichtenstein, 2004;Lichtenstein et al, 2005). The Deep South is also home to comparatively more groups experiencing health inequities (Minority Health Initiatives, 2006; and has a long and persistent history of disparities based on gender and economic class (Collins, 2000;Royster et al, 2006).…”
Section: Introductionmentioning
confidence: 99%